2021
DOI: 10.1016/j.tics.2020.12.007
|View full text |Cite
|
Sign up to set email alerts
|

The Continuity of Context: A Role for the Hippocampus

Abstract: Tracking moment-to-moment change in input, and detecting change sufficient to require altering behavior is crucial to survival. We discuss how the brain evaluates change over time, focusing on hippocampus and its role in tracking context. We leverage the anatomy and physiology of the hippocampal longitudinal axis, re-entrant loops, and amorphous networks, to account for stimulus equivalence and the updating of an organism's sense of it's context. Place cells play a central role in tracking contextual continuit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 81 publications
0
40
0
Order By: Relevance
“…It should be appreciated that a single synaptic event can have rhythmic entrainment to both "theta" and "gamma" bands, challenging the heuristic of independence across rhythms. Instead, the dynamic patterns in the LFP are closely related to how the activity spatio-temporally evolves a reentrant network (Berg et al, 2019;Maurer and Nadel, 2021). While there is comfort in giving independence to specific patterns like theta and gamma, neurobiology makes no such distinction.…”
Section: Discussionmentioning
confidence: 99%
“…It should be appreciated that a single synaptic event can have rhythmic entrainment to both "theta" and "gamma" bands, challenging the heuristic of independence across rhythms. Instead, the dynamic patterns in the LFP are closely related to how the activity spatio-temporally evolves a reentrant network (Berg et al, 2019;Maurer and Nadel, 2021). While there is comfort in giving independence to specific patterns like theta and gamma, neurobiology makes no such distinction.…”
Section: Discussionmentioning
confidence: 99%
“…In keeping with this observation, recent comparisons of dorsal and ventral hippocampal lesions in the MWT have shown that while dorsal lesions impair precise localization of goal locations, ventral damage impairs coarse localization in the MWT [16-18]. In relation to cellular recruitment, it is anticipated that cells in the dorsal hippocampus are more likely to be recruited due to a greater number of small place fields that would be required to tesselate a space than those with large fields in ventral hippocampus [6, 7]. Indeed, multiple groups have found that place cells in the dorsal hippocampus have multiple fields in large environments [46-50].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the dorsal region is said to be necessary for spatial navigation and memory, and the ventral region is important for emotional processing [2, 4]. An alternative view, largely informed by the observation that place field size increases from dorsal to ventral regions, posits instead that the hippocampal longitudinal axis varies in its granularity of representation, wherein spatial-temporal resolution of representation decreases along the axis, ventrally [5-7].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, forgetting irrelevant experiences might be an adaptive biological process (Hardt et al, 2013) and resonates with the idea that the brain should form compact memory representations that have the highest utility for behavior. Tackling the question of what counts as an event or experience, a common theme in neuroscience has been to posit that the brain segments continuous experience into representations of distinct neural states that transition at boundaries between events or shifts in context (for reviews, see e.g., Richmond & Zacks, 2017;Brunec et al, 2018;Shin & DuBrow, 2020;Bird, 2020;Maurer & Nadel, 2021), a process that might also happen retroactively, after experiences have been obtained (Clewett et al, 2019). This formation of segmented memory traces is thought to be driven by various factors, including inferred changes in the environment (DuBrow et al, 2017), prediction error signals elicited by reward outcomes (Rouhani et al, 2020) or discontinuities in the statistical structure of the environment (Gershman et al, 2014).…”
Section: Box 2 What Is Replayed?mentioning
confidence: 99%